Inhibition of the ʟ-glutamine transporter ASCT2 sensitizes plasma cell myeloma cells to proteasome inhibitors. (1st June 2021) - Prelowska, Monika K.; Mehlich, Dawid; Ugurlu, M. Talha; Kedzierska, Hanna; Cwiek, Aleksandra; Kosnik, Artur; Kaminska, Klaudia; Marusiak, Anna A.; Nowis, Dominika
Abstract: Proteasome inhibitors (PIs), used in the treatment of plasma cell myeloma (PCM), interfere with the degradation of misfolded proteins leading to activation of unfolded protein response (UPR) and cell death. However, despite initial strong antimyeloma effects, PCM cells eventually develop acquired resistance to PIs. The pleiotropic role of ʟ-glutamine (Gln) in cellular functions makes inhibition of Gln metabolism a potentially good candidate for combination therapy. Here, we show that PCM cells, both sensitive and resistant to PIs, express membrane Gln transporter (ASCT2), require extracellular Gln for survival, and are sensitive to ASCT2 inhibitors (ASCT2i). ASCT2i synergistically potentiate the cytotoxic activity of PIs by inducing apoptosis and modulating autophagy. Combination of ASCT2 inhibitor V9302 and proteasome inhibitor carfilzomib upregulates the intracellular levels of ROS and oxidative stress markers and triggers catastrophic UPR as shown by upregulated spliced Xbp1 mRNA, ATF3 and CHOP levels. Moreover, analysis of RNA sequencing revealed that the PI in combination with ASCT2i reduced the levels of Gln metabolism regulators such as MYC and NRAS . Analysis of PCM patients' data revealed that upregulated ASCT2 and other Gln metabolism regulators are associated with advanced disease stage and with PIs resistance. Altogether, we identified a potent therapeutic approach that may prevent acquired resistance to PIs and may contribute to the improvement of treatment of patients suffering from PCM. Highlights: Plasma cell myeloma (PCM) cells express ASCT2 Gln transporter and rely on extracellular l -glutamine. In PCM cells ASCT2 inhibitors potentiate cytotoxic activity of proteasome inhibitors (PIs). Combination treatment induces oxidative stress leading to catastrophic unfolded protein response, apoptosis and autophagy. Upregulated Gln metabolism modulators are associated with advanced disease stage and with PIs resistance.